From crisis to change: exploring the lasting influence of COVID-19 on Airbnb users through structural topic modeling - Kai Ding; Yang Bao; Le Li; Rongteng Renata Zhang; Yuhua Chen (Humanities & Social Sciences Communications)
Abstract A key challenge for the peer-to-peer (P2P) accommodation industry is keeping pace with the evolving expectations and behavior of guests over time, shaped by diverse experiences and shifting preferences. This study employs advanced text analytics to analyze the enduring impact of COVID-19 on Airbnb users’ accommodation preferences, both during the pandemic and in the subsequent year, covering the period from May 2020 to May 2024. Employing a longitudinal research design, we analyze a dataset of 461,509 reviews from 18,465 listed properties across four major cities in different countries (i.e., Spain, the United Kingdom, and the United States) known for their Airbnb presence. Our findings highlight that the most significant and enduring impact of the pandemic on guest behavior is an increased prioritization of health-related features. Although certain attributes that were previously valued remain relevant, there has been a marked transition in user perceptions; specifically, hedonic and aesthetic values have diminished in importance relative to health-centric considerations and psychological well-being. Furthermore, the policies and practices adopted during the pandemic reveal additional dimensions of its lasting influence, shaping guest expectations and preferences. Notably, these include enhanced booking and cancellation flexibility, the implementation of contactless services, and the provision of protective equipment. This research contributes to understanding how crises can reshape guest priorities within the context of sharing economy accommodations, offering valuable insights for both academic researchers and practitioners.